I shop, therefore I am: Barbara Kruger - Val Cubero, Alejandra (Cuestiones de Género: de la igualdad y la diferencia, 2012)
The artist Barbara Kruger graduated from The Parson Design School in New York was fed from feminist currents of the 70’s and 80’s. She used advertising techniques with the employment of direct, short and shocking slogans, in shades of red and black. She used the language of the media to criticize, for more than four decades, the consumer society and gender relations aspects. Currently, her work has been phagocytized by the art market and it’s necessary to open up new paths that know the logic of commercial advertising, in order to subvert them.